1996
DOI: 10.1161/01.atv.16.10.1222
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholesterol Feeding Suppresses Human Cholesterol Synthesis Measured by Deuterium Incorporation and Urinary Mevalonic Acid Levels

Abstract: The objective of this study was to measure the response of cholesterol biosynthesis in subjects to three different amounts of dietary cholesterol: 50 (low), 350 (medium), and 650 (high) mg cholesterol per 2800 kcal. Individuals with low (n = 7), normal (n = 12), and elevated (n = 11) plasma cholesterol concentrations consumed in random order solid-food test diets (15%, 55%, and 30% of energy as protein, carbohydrate, and fat, respectively) at each dietary cholesterol level. The three diets were consumed for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 40 publications
2
57
0
6
Order By: Relevance
“…Dietary cholesterol has been shown to regulate HMGCoA reductase activity by feedback inhibition (43)(44). Egg yolk supplemented high cholesterol diets not only increased plasma cholesterol levels but also decreased urinary mevalonate excretion in our experiments.…”
Section: Downloaded Fromsupporting
confidence: 53%
“…Dietary cholesterol has been shown to regulate HMGCoA reductase activity by feedback inhibition (43)(44). Egg yolk supplemented high cholesterol diets not only increased plasma cholesterol levels but also decreased urinary mevalonate excretion in our experiments.…”
Section: Downloaded Fromsupporting
confidence: 53%
“…A possible mechanism was reported that early cholesterol exposure suppressed endogenous cholesterol synthesis even in later life. 25 The present study suggested that infants with younger gestational age did not have enough cholesterol exposure in neonatal period, when they were given formula milk. Additional longitudinal studies are necessary to determine whether the effect of gestational age on LDL profile persists into adulthood or changes with age, as observed in TC concentrations in breast-fed adults.…”
Section: Discussionmentioning
confidence: 58%
“…Although we did not directly measure hepatic LDL receptor and HMGCoA reductase mRNA levels, previous studies have demonstrated an excellent correlation between the hepatic and monocyte values (51). Since one would anticipate that there would be a reciprocal relationship between FSR/HMG-CoA reductase mRNA levels and cholesterol absorption (52)(53)(54), it is reassuring to see that without changes in absorption, these other measurements did not change, thereby serving as an internal validation for each other. Interestingly, the absence of change in plasma cholesterol concentration might not be unexpected in normolipemic subjects, because the greatest UDCA-dependent reductions in plasma cholesterol concentrations occurred in patients with the highest plasma cholesterol concentrations (55,56).…”
Section: Effect Of Udca On Cholesterol Metabolismmentioning
confidence: 85%